SITUATIONAL CONTEXT ANALYSIS OF APOLOGY IN BANGGAI LANGUAGE - Asyrafunnisa Asyrafunnisa; Rahmayani Irma (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This research aims to know the sentences of apology in Banggai language. In addition to knows the meaning of the sentences of apology in Banggai, the writer also will explain the function of the sentences mentioned. This research used the qualitative research. Qualitative research methods are methods that emphasize more on the aspect of deep understanding of a problem than to see the problem for generalization research. This research prefers to use in- depth analytical technique, that is to examine problem in case of problem. Result of the research show that sentences of apology in Banggai language has some kind as follow: apology to Allah SWT, for parent, King, friend, husband-wife, and Brother